A new Cathaysiorthis (Brachiopoda) fauna from the lower Llandovery of eastern Qinling, China. (13th March 2019) - Huang, Bing; Harper, David A. T.; Zhou, Hang‐Hang; Zhan, Ren‐Bin; Wang, Yi; Tang, Peng; Ma, Jun‐Ye; Wang, Guang‐Xu; Chen, Di; Zhang, Yu‐Chen; Luan, Xiao‐Cong; Rong, Jia‐Yu
Abstract: Following the end Ordovician mass extinction, brachiopod faunas were commonly of low diversity, generally rare in abundance, and restricted to shallow‐water environments in many places. The Cathaysiorthis fauna, first described from South East China, is the most diverse brachiopod fauna in the world succeeding the Hirnantia fauna, and has modified our previous views on the recovery of shelly benthos after the extinctions. Here, we report a newly‐discovered fauna with abundant Cathaysiorthis from the lower Zhangwan Formation (lower–middle Rhuddanian, lower Llandovery) in Qinling, Xichuan County, Henan Province, China. This fauna is slightly younger than that previously documented from South East China, and the evolution of Cathaysiorthis fauna, in terms of its composition, is discussed. The Qinling Cathaysiorthis fauna has a narrower bathymetric range (Benthic Assemblage Zone 3) than that of the fauna from South East China (BA 2–5) and occurred on the Qinling–Dabie Microplate located on the northwest margin of the South China Plate. The migration of the Cathaysiorthis fauna from the South China plate to Qinling–Dabie was achieved by larvae that used ambient ocean currents and possibly drifted from the Jiangnan Region of South East China to Qinling. The Qinling Cathaysiorthis fauna includes 13 species belonging to 12 genera. Two new species, Cathaysiorthis xichuanensis sp. nov. and Aegiria apta sp. nov. are established and described herein, and ten other species are discussed.